Pengaruh Rasio Likuiditas, Solvabilitas, Profitabilitas Terhadap Harga Saham Subsektor Perkebunan Yang Terdaftar Di Bursa Efek Indonesia - Eka Sholeha Thea; hari sulistyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Share Price is a reflection of the successful management of the company. A high share price will provide benefits, namely in the form of capital gains and a better image for the company so that it will attract investors to invest in the company. This study aims to determine whether there is an influence between liquidity, solvency and profitability on stock prices either partially or simultaneously. The research sample taken was 11 companies from a total of 19 plantation subsector companies that were listed on the Indonesia Stock Exchange in 2016-2018 with the sampling technique used was purposive sampling technique. The research method used is descriptive and verification, where descriptive uses descriptive statistics and verification uses multiple linear regression analysis and the coefficient of determination. The results of this study partially Current Ratio has no effect on stock prices, Debt to Equity Ratio has a negative effect on stock prices and Return on Equity has negative effects on stock prices. Keywords: Stock Price, Liquidity, Solvency, Profitability